Studies on some aspects of myxosporidia infection of gill tissues in Cyprinus carpio - Thiruchelvam s/o A.T. Arasu (Fakulti Pengajian Maritim dan Sains Marin, 2011)
This study on Myxosporidian infection in common carp(Cyprinus carpio) was prompted due to its recent introduction into the country.